Bond durability of BFRP bars embedded in concrete with fly ash in aggressive environments. (1st September 2021) - Lu, Zhongyu; Su, Lizhu; Lai, Jiawei; Xie, Jianhe; Yuan, Bing
Abstract: Fiber-reinforced polymer (FRP) bars are an environmentally friendly alternative to steel and are considered ideal substitutes for steel reinforcement in marine concrete structures due to their excellent resistance to chloride ions and mechanical properties. However, the strong alkaline environment in concrete results in the degradation of FRP bars, and the degradation of FRP bars is detrimental to the long-term performance of these structures due to the decrease in interfacial bonding. This study aims to investigate the bond durability of basalt FRP (BFRP) bar and concrete with or without fly ash in corrosion environments by pull-out tests. The laboratory-accelerated aging environments are an alkaline solution (pH 12.8 ± 0.2) and simulated seawater, and the immersion temperatures are set at room temperature ( 26 °C), 40 °C, and 60 °C. Furthermore, the mechanical properties of the BFRP bars are also determined under the same conditions. Results indicate that the mechanical properties of the BFRP bars and the bond strength decrease as the immersion time increases. The addition of fly ash in concrete can improve the interfacial bond strength. For instance, the bond strength of BFRP-ordinary concrete decreases by 69.0% when immersed in a 60 °C alkaline solution for 6 months, and that of BFRP-fly ash concrete decreases by 58.1% in the same immersion environment. The similar experimental phenomenon can also be obtained in seawater, which can be attributed to fly ash refining the concrete pores and inhibiting the reaction of alkaline with silica contained in the basalt fibers. Finally, the retention of bond strength is predicted based on the apparent horizontal shear strength of the BFRP.